2017
DOI: 10.1186/s40635-017-0162-1
|View full text |Cite
|
Sign up to set email alerts
|

An experimental model to measure the ability of headphones with active noise control to reduce patient’s exposure to noise in an intensive care unit

Abstract: BackgroundDefining the association between excessive noise in intensive care units, sleep disturbance and morbidity, including delirium, is confounded by the difficulty of implementing successful strategies to reduce patient’s exposure to noise. Active noise control devices may prove to be useful adjuncts but there is currently little to quantify their ability to reduce noise in this complex environment.MethodsSound meters were embedded in the auditory meatus of three polystyrene model heads with no headphones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
0
9
0
2
Order By: Relevance
“…Noise-canceling headsets can deliver personalized music in addition to reducing noise exposure. 59 Another option is the use of directional speakers which allow for individualized music selection without excessively disturbing neighboring patients. These can be installed either in the patient's vicinity (e.g., around pillow) or through bed-or ceiling-mounted versions.…”
Section: Innovations In Sound Controlmentioning
confidence: 99%
“…Noise-canceling headsets can deliver personalized music in addition to reducing noise exposure. 59 Another option is the use of directional speakers which allow for individualized music selection without excessively disturbing neighboring patients. These can be installed either in the patient's vicinity (e.g., around pillow) or through bed-or ceiling-mounted versions.…”
Section: Innovations In Sound Controlmentioning
confidence: 99%
“…Perceived night-time noise was improved, but with no effect on sleep quality or use of delirium Our full-text review and data extraction appraised articles studying single-component noise control strategies, such as behavioral programs [62][63][64][65][66] , earplugs or noise cancelling headphones [67][68][69][70][71] , and headphones equipped with an alarm filtering system 72 ; however these were not included since they reviewed the impact of interventions on the level of noise or quality of sleep, but delirium was not reported as an outcome (Excluded studies; Supplementary Table 3).…”
Section: Noise Modificationmentioning
confidence: 99%
“…Without substantially altering the clinical staff's responsibilities, non-pharmaceutical sleep-promoting interventions such as earplugs and eye masks were found to have some benefit on sleep and prevention of delirium [43]. Another study by Gallacher et al found that noise-canceling headphones reduced sound exposure by a mean 6.8 dB for a patient [44]. This reduction does not necessarily decrease the sound environment down to the WHO accepted 30 dB, but it is nonetheless an improvement.…”
Section: Reduce Patient Exposure To Alarmsmentioning
confidence: 99%